Managing online risk : apps, mobile, and social media security - Gonzalez, Deborah (Butterworth-Heinemann, 2015)
In recent years, building a corporate online presence has become nonnegotiable for businesses, as consumers expect to connect with them in as many ways as possible. There are benefits to companies that use online technology, but there are risks as well. Managing Online Risk presents the tools and resources needed to better understand the security and reputational risks of online and digital activity, and how to mitigate those risks to minimize potential losses. Managing Online Risk highlights security and risk management best practices that address concerns such as data collection and stora.